Oral and Systemic Health Findings of Orofacial Susuk Users (Preliminary Study in Jakarta, Indonesia) - Manuel Dwiyanto Hardjo Lugito (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: Susuk (Charm needles) are talisman small metal needles that are inserted subcutaneously, widely practiced in Malaysia, Brunei, Singapore, Thailand, and Indonesia, and believed to enhance beauty, youth, charisma, strength, or health, or bring success in business of users. Method: This study was a descriptive, cross-sectional study. All of outpatients in one of Hospital in West Jakarta, Indonesia from January to June 2025 who were referred for dental treatment and underwent routine radiological examinations were included. The length and diameter of susuk was calculated based on the comparison formula. The age, gender, facial pain, DMF-T, and health status were examined and recorded. The length and diameter of susuk was calculated based on the comparison formula. The age, gender, facial pain, DMF-T, and health status were examined and recorded. Data is summarized and processed to be presented as a descriptive statisticResult: A total of 6 females and 2 males were using susuk with an average age of 65.125+7.149 years consist of 3 females and 1 male had 1 susuk, 1 male and 2 females had 2 susuk, 1 female had 7 susuk. Orbicularis oris is the most common location of susuk, 1 female with Bell’s Palsy was reported. Mean of DMF-T was 14.5+6.1; Type 2 Diabetes was found in 5 users, hyperthyroid in 2 users; with other diseases such as joint inflammation and hypertension. Conclusion: Orofacial susuk users were elderly and mostly women with DMF-T index were very high and suffer from several comorbidities.